Do Firm Value and Institutional Investors Affect on Herding Behavior? - Fenny Marietza; Salsabila Tifani Ayuningsih (Riset Akuntansi dan Keuangan Indonesia, 2022)
This research aims to determine the effect of firm value and institutional investors on herding behavior. The newnes of this research to add an indicator that have never been used for herding measurement to firm value. The existence of previous research result on herding that have not been conclusive raise empirical gaps and population gaps that are worthy of re-study. The measurement of firm value is carried out using the Book to Market Ratio and Firm Size. The size of institutional investors uses the company's institutional ownership, and the measurement of herding behavior uses the Cross-Sectional Absolute Deviation (CSAD) method. The sample in this study are LQ45. The data analysis method used in this study was carried out with multiple regression analysis. The study results show that there is indication of the occurrence of Herding Behavior in LQ45 companies in sample. Firm Value and institutional investors do not influence Herding Behavior. Keywords: Herding Behavior, Firm Value, Institutional Investors, LQ45 Companies